factorize 47 th question
Attachments:
![](https://hi-static.z-dn.net/files/dbd/b1ab26b41eaa8d487edbb1f2e6f5ab18.jpg)
Answers
Answered by
5
Hello,
The polynomial is :-
![4 {x}^{3} + 20 {x}^{2} + 33x + 18 \\ 4 {x}^{3} + 20 {x}^{2} + 33x + 18 \\](https://tex.z-dn.net/?f=4+%7Bx%7D%5E%7B3%7D++%2B+20+%7Bx%7D%5E%7B2%7D++%2B+33x+%2B+18+%5C%5C)
It is a cubic polynomial.
Hence to solve it or factorize it we need to use the trial and error method.
P(x) = 4x³+20x²+33x+18
P(-1) = 4(-1)³+20(-1)²+33(-1)+18
= - 4+20-33+18 = - 37 + 38 =1
P(-2) = 4(-2)³+20(-2)²+33(-2)+18
= - 32 + 80 - 66 -+18
= - 98+98 =0
So p(-2) =0
By factor theorem we can say that
X+2 is a factor of p(x)
Now,
We will divided p(x) by (x+2)
See the division in the attachment :
So p(x) = (x+2)(4x²+12x+9)
Now we will do middle term splitting of the second product of p(x) that is (4x²+12x+9)
See the attachment for splitting...
After splitting we got
P(x) = (x+2)(2x+3)(2x+3)
This is the factorization of 47 th number
Hope this will be helping you ✌️
The polynomial is :-
It is a cubic polynomial.
Hence to solve it or factorize it we need to use the trial and error method.
P(x) = 4x³+20x²+33x+18
P(-1) = 4(-1)³+20(-1)²+33(-1)+18
= - 4+20-33+18 = - 37 + 38 =1
P(-2) = 4(-2)³+20(-2)²+33(-2)+18
= - 32 + 80 - 66 -+18
= - 98+98 =0
So p(-2) =0
By factor theorem we can say that
X+2 is a factor of p(x)
Now,
We will divided p(x) by (x+2)
See the division in the attachment :
So p(x) = (x+2)(4x²+12x+9)
Now we will do middle term splitting of the second product of p(x) that is (4x²+12x+9)
See the attachment for splitting...
After splitting we got
P(x) = (x+2)(2x+3)(2x+3)
This is the factorization of 47 th number
Hope this will be helping you ✌️
Attachments:
![](https://hi-static.z-dn.net/files/d7b/d3c74786a616bb97dc99e86279e8a415.jpg)
![](https://hi-static.z-dn.net/files/da2/1c4a8ef1fd8ac2513f9ac752947a7c39.jpg)
Anonymous:
Great
Similar questions